Tính
a) \(\frac{-1}{7}.\left(9\frac{1}{2}-8,75\right):\frac{2}{7}+0,625:1\frac{2}{3}\)
b)x-25%.x-1=-|-5|
c)\(2\frac{3}{4}.\left(0,4\right)1\frac{3}{5}.2,75+\left(-1,2\right):\frac{4}{11}\)
d) (2,8 x -32 ):\(\frac{2}{3}=-90\)
Tính:
A=\(\left(1-\frac{2}{3}+\frac{4}{3}\right)-\left(\frac{4}{5}-1\right)+\left(\frac{7}{5}+2\right)\)
B=\(\left(-3+\frac{3}{4}-\frac{1}{3}\right):\left(5+\frac{2}{5}-\frac{2}{3}\right)\)
C=\(\left(\frac{3}{5}-\frac{4}{15}\right).\left(\frac{2}{7}-\frac{3}{14}\right)-\left(\frac{5}{9}-\frac{7}{27}\right)\)\(.\left(1-\frac{3}{5}\right)+\left(1-\frac{11}{12}\right).\left(1+\frac{11}{12}\right)\)
D=\(\frac{\left(\frac{3}{10}-\frac{4}{15}-\frac{7}{20}\right).\frac{-5}{19}}{\left(\frac{1}{14}+\frac{1}{7}-\frac{-3}{35}\right).\frac{4}{3}}\)
A = \(26:[\frac{(3:10,2-0,1)}{25.\left(0,8+1,2\right)}+\frac{\left(34,06-33,81\right).4}{6,84:\left(38,57-25,15\right)}]+\frac{2}{3}:\frac{4}{21}\)
B = \(\frac{0,8:\left(\frac{4}{5}.1,25\right)}{0,64-\frac{1}{25}}+\frac{\left(1,08-\frac{2}{25}\right):\frac{4}{7}}{(6\frac{5}{9}-3\frac{1}{4}).2\frac{2}{17}}+\left(1,2.0,5\right)\)
Tính
a,\(\frac{2^{10}\cdot55+2^{10}\cdot26}{2^8\cdot27}\)
b,120:{300:[150-(2.53-23.25)]}
c,\(\left[\left(\frac{40}{130}-\frac{12}{13}\right)\cdot40\%+0,15\right]:\frac{-5}{52}\)
d,\(\frac{0,8:\left(\frac{4}{5}\cdot1,25\right)}{0,64-\frac{1}{25}}+\frac{\left(1,08-\frac{2}{25}\right):\frac{4}{7}}{\left(6\frac{5}{9}-3\frac{1}{4}\right)\cdot2\frac{2}{17}}+\left(1,2+0,5\right):\frac{1}{5}\)
Đề bài: Bỏ dấu ngoặc rồi nhóm các số hạng thích hợp
\(A=\left(-7+\frac{3}{4}-\frac{1}{3}\right)-\left(6-\frac{5}{4}+\frac{4}{3}\right)-\left(3+\frac{7}{4}-\frac{5}{3}\right)\)
\(B=\left(6+\frac{2}{3}-\frac{1}{2}\right)-\left(5-\frac{5}{3}+\frac{3}{2}\right)-\left(3+\frac{7}{3}-\frac{5}{2}\right)\)
A=\(\frac{\left(3\frac{2}{15}+\frac{1}{5}\right):2\frac{1}{2}}{\left(5\frac{3}{7}-2\frac{1}{4}\right):4\frac{43}{56}}\)
B=\(\frac{1,2:\left(1\frac{1}{5}.1\frac{1}{4}\right)}{0,32+\frac{2}{25}}\)
CMR: A=B
A=\(\frac{\left(3\frac{2}{15}+\frac{1}{5}\right):2\frac{1}{2}}{\left(5\frac{3}{7}-2\frac{1}{4}\right):4\frac{43}{56}}\)
B=\(\frac{1,2:\left(1\frac{1}{5}.1\frac{1}{4}\right)}{0,32+\frac{2}{25}}\)
Cho A = \(\frac{\left(3\frac{2}{5}+\frac{1}{5}\right):2\frac{1}{2}}{\left(5\frac{3}{7}-2\frac{1}{4}\right):4\frac{43}{56}}\); B = \(\frac{1,2:\left(1\frac{1}{5}-1\frac{1}{4}\right)}{0,32+\frac{2}{25}}\)
So sánh A và B
Cho A = \(\frac{\left(3\frac{2}{5}+\frac{1}{5}\right):2\frac{1}{2}}{\left(5\frac{3}{7}-2\frac{1}{4}\right):4\frac{43}{56}}\)và B = \(\frac{1,2:\left(1\frac{1}{5}-1\frac{1}{4}\right)}{0,32+\frac{2}{25}}\)
So sánh A và B